Bimetallic selenium/zinc oxide nanoparticles: biological activity and plant biostimulant properties - Samy Selim; Amna A. Saddiq; Ruba Abdulrahman Ashy; Afra Mohammed Baghdadi; Ashwag Jaman Alzahrani; Ehab M. Mostafa; Soad K. Al Jaouni; Mohammed Yagoub Mohammed Elamir; Mohamed A. Amin; Ahmed M. Salah; Nashwa Hagagy (AMB Express)
Abstract Extracts of medicinal seeds can be used to synthesize nanoparticles (NPs) in more environmentally friendly ways than physical or chemical ways. For the first time, aqueous extract from unexploited grape seeds was used in this study to create Se/ZnO NPS utilizing a green technique, and their antimicrobial activity, cytotoxicity, antioxidant activities, and plant bio stimulant properties of the economic Vicia faba L. plant were evaluated. Se/ZnO NPS is characterized by SEM and TEM images, FTIR, and XRD. Through the well diffusion assay and the scavenging of 1,1-Diphenyl-2-picrylhydrazyl (DPPH) free radical experiment, biogenic Se/ZnO NPs demonstrated their antibacterial and antioxidant activities. The nanomaterial compound showed the highest inhibitory effects of 99.7, 55.63, 16.91, 10.25, 6.61, 3.83, 3.00, and 2.59%, respectively, against the cervical carcinoma (SKOV3 cells) cell line at conc of 7.81, 15.62, 31.25, 62.5, 125, 250, 500, and 1000 µg/ml, respectively, with IC50 values at 20.31 µg, resulting in 50% cell death. This study demonstrated the value of bimetallic nano-fertilizers Se/Zn in promoting faba bean development, yield features, and metabolite contents (protein, phenol, carbs, and pigments). These fertilizers are probably also advantageous for other crops. When applied in contrast to the control, 100 ppm of biological nano-Se/ZnO may generally result in the best growth and yield of faba beans. Further research is needed on the ecological aspect of biological nanofertilizers in addition to the economic one.